Second-Line Protease Inhibitor-Based Haart after Failing Non-Nucleoside Reverse Transcriptase Inhibitor-Based Regimens in Asian HIV-Infected Children. Issue 4 (May 2013) - Bunupuradah, Torsak; Puthanakit, Thanyawee; Fahey, Paul; Kariminia, Azar; Yusoff, Nik KN; Khanh, Truong H; Sohn, Annette H; Chokephaibulkit, Kulkanya; Lumbiganon, Pagakrong; Hansudewechakul, Rawiwan; Razali, Kamarul; Kurniati, Nia; et al.
Background: The World Health Organization (WHO) recommends boosted protease inhibitor (bPI)-based HAART after failing non-nucleoside reverse transcriptase inhibitor (NNRTI) treatment. We examined outcomes of this regimen in Asian HIV-infected children. Methods: Children from five Asian countries in the TREAT Asia Pediatric HIV Observational Database (TApHOD) with ≥24 weeks of NNRTI-based HAART followed by ≥24 weeks of bPI-based HAART were eligible. Primary outcomes were the proportions with virological suppression (HIV RNA<400 copies/ml) and immune recovery (CD4 + T-cell percentage [CD4%]≥25% if age <5 years and CD4 + T-cell count ≥500 cells/mm 3 if age ≥5 years) at 48 and 96 weeks. Results: Of 3, 422 children, 153 were eligible; 52% were female. At switch, median age was 10 years, 26% were in WHO stage 4. Median weight-for-age z-score (WAZ) was -1.9 ( n =121), CD4% was 12.5% ( n =106), CD4 + T-cell count was 237 cells/mm 3 ( n =112), and HIV RNA was 4.6 log10 copies/ml ( n =61). The most common bPI was lopinavir/ritonavir (83%). At 48 weeks, 61% (79/129) had immune recovery, 60% (26/43) had undetectable HIV RNA and 73% (58/79) had fasting triglycerides ≥130 mg/dl. By 96 weeks, 70% (57/82) achieved immune recovery, 65% (17/26) had virological suppression, and hypertriglyceridaemia occurred in 66% (33/50). Predictors for virological suppression at week 48 were longer duration of NNRTI-based HAART ( P =0.006), younger age ( P =0.007), higher WAZ ( P =0.020) and HIV RNA at switch <10, 000 copies/ml ( P =0.049). Conclusions: In this regional cohort of Asian children on bPI-based second-line HAART, 60% of children tested had immune recovery by 1 year, and two-thirds had hyper-lipidaemia, highlighting difficulties in optimizing second-line HAART with limited drug options.